The Hungarian peach production risks - Persely, Sz. (International Journal of Horticultural Science, 2010)
Hungary possesses very good agroecological conditions even in a European comparison. Agriculture and food production is highly important despite its decreasing relative economic significance, since providing high quality and affordable food for the population is a basic social necessity and one of the decisive factors in quality of life. The development of vegetable and fruit production is of great importance both from a healthy nutrition as well as from a comparative advantage (cheap labour, expertise, production traditions, favourable climate) point of view.Vegetable and fruit consumption per capita is lower than in developed countries, which is a decisive indicator of healthy nutrition, but improvement is continuous and desired. Appropriate quality and quantity in production is a requirement to meet customers’ needs in a highly competitive market from one year to the next. Hungary can only be competitive if production results are improved while risks are reduced. Fruit production is a sector with high capital requirements, risk assessment is very important from a production, investment as well as from a national economy point of view. Our examinations will focus on production risk, which is present in the annual fluctuation of average yields, especially as a result of extreme weather factors.